2001
DOI: 10.1001/archpedi.155.4.501
|View full text |Cite
|
Sign up to set email alerts
|

Use of Inhaled Anti-inflammatory Medication in Children With Asthma in Managed Care Settings

Abstract: There may be differences in the use of preventive asthma medication in children that are affected by age, sex, and health care organization. Few children with frequent symptoms are using controllers regularly, as is recommended by national guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 30 publications
2
38
0
Order By: Relevance
“…Younger age was also associated with severe exacerbations in the study by Covar et al 8 Previous studies have found that predictors of experiencing severe exacerbations are being treated with inhaled corticosteroids, 28 having had previous histories of ED visits or hospitalizations, 13,[29][30][31] or having had treatment in the past with oral corticosteroids. 30 The previous fi ndings that treatment with inhaled corticosteroids is a predictor of severe 2007 NAEPP recommendations for assessing risk and impairment separately.…”
Section: Discussionmentioning
confidence: 87%
“…Younger age was also associated with severe exacerbations in the study by Covar et al 8 Previous studies have found that predictors of experiencing severe exacerbations are being treated with inhaled corticosteroids, 28 having had previous histories of ED visits or hospitalizations, 13,[29][30][31] or having had treatment in the past with oral corticosteroids. 30 The previous fi ndings that treatment with inhaled corticosteroids is a predictor of severe 2007 NAEPP recommendations for assessing risk and impairment separately.…”
Section: Discussionmentioning
confidence: 87%
“…Previous studies have identified variables associated with asthma care processes or outcomes by measuring the characteristics of patients and clinicians. 3,18,[20][21][22][23][24] However, research that evaluates variables from practice sites or that combines variables from practice sites, clinicians, and patients is uncommon, perhaps because of the complexity of identifying the interrelationships among these entities, then collecting and linking data from multiple classes of respondents.…”
Section: Major Findingsmentioning
confidence: 99%
“…Information on this relationship was deduced from one of several outcomes measured in the body of the study. Those few studies that primarily analyzed this relationship were two studies by Kozyrskyj et al [5,6], one study Adams et al [7] one study by Hong & Shepherd [8] and one study by Finkelstein et al [9]. The studies and their findings are described in detail below according to theme.…”
Section: Impact Of Family Incomementioning
confidence: 99%
“…The study by Adams et al (2001) looked at asthma medication usage patterns by age, sex, and health care organization. The 13,352 children in this study were enrolled in one of 4 U.S. managed care organizations (MCO's) that participated in the PAC-PORT II study, which was a multi-center pediatric asthma trial of strategies to improve pediatric asthma health outcomes [7].…”
Section: Type Of Insurance Provider Plan or Cost-sharing Mechanismmentioning
confidence: 99%
See 1 more Smart Citation